EVALUATION OF THE IMPLEMENTATION OF ADDITIONAL PUBLIC SERVANTS' INCOME TO THE EDUCATION AND TRAINING STAFFING AGENCY OF NORTH TORAJA REGENCY - Parung, Antonius Tangke (Jurnal Administrasi Negara, 2020)
The purpose of this study is to evaluate the implementation of additional civil servant income in the North Toraja District Education and Training Personnel Agency with a focus on evaluating the implementation of additional civil servant income in terms of policies and supporting infrastructure. The research method used in this study is a qualitative method with the type of case study research to provide a written description of how the implementation of providing additional income for Civil Servants at the North Toraja District Education and Training Personnel Agency, so that the implementation is in accordance with the stated objectives. The results showed that: (1) The provision of TPP although the amount is very small but can increase the income of civil servants (72% PNS on BKPP agreed); (2) Measurement and assessment of work performance of the working target element is not optimal; (3) Electronic attendance equipment has not been integrated with the system so that the realization of work behavior (presence) of PNS is not objective; (4) The policy in this case the Bupati regulation as the basis for the provision of TPP should be revised in order to contain weight reduction for the late and returning civil servants.